The Overseas Listing of Chinese Enterprises: Reasons and Choices of Listing Locations - Cai, Shuo (2008)
Abstract As a large number of Chinese enterprises go abroad, overseas listing has increasingly become one of the key issues that need to be considered for Chinese enterprises during their development process. This paper aims to research why Chinese enterprises need to get listed at overseas exchanges and why Hong Kong should be the key listing market.